Peran Pendidikan Kewarganegaraan dalam Mencegah Radikalisme di Kalangan Remaja Gen Z - Arianti, Aisyah; Salsabilla, Echa; Adhim, Mohammad Fauzil; Hendri, Nazsa Anugerah Widia; Fitri, Nasyatul Aulia; Febriani, Selpi; Hudi, Ilham (Lembag, 2024)
This research examines the role of citizenship education in preventing radicalism among Generation Z teenagers in Indonesia. Using literature study methods, this research analyzes various literature sources to understand the challenges faced by Generation Z, the radicalization process, and the effectiveness of citizenship education as a prevention instrument. The research results show that Generation Z, as digital natives, is vulnerable to exposure to radical ideology through social media and the internet. Civic education plays an important role in instilling the values ​​of tolerance, diversity and critical thinking, which can act as an ideological bulwark against radicalism. This research concludes that strengthening citizenship education is a key strategy in building youth resilience against radicalism and promoting an inclusive and harmonious society.